Assessing pharmacy student experience with, knowledge of and attitudes towards harm reduction: illuminating barriers to pharmacist-led harm reduction - Lily Rowan Mahon; Amanda N. Hawthorne; Julie Lee; Heather Blue; Laura Palombi (BMC, 2018)
Abstract Background As the burden from the opioid epidemic continues to increase in the state of Minnesota and across the nation, the University of Minnesota College of Pharmacy seeks to design an innovative, comprehensive harm reduction curriculum in order to better train student pharmacists to serve the varied needs of the greater community. This study examines incoming individuals' baseline knowledge of and attitudes toward harm reduction in order to better inform curriculum planning and to ultimately produce pharmacists capable of impacting the devastating effects of the opioid crisis. Methods Incoming first-year pharmacy students took a survey focused on their knowledge of opioid overdose and the drug naloxone and also provided written reflections on their perceptions of harm reduction. Data was coded using consensual qualitative research (CQR) into appropriate domains. Results Pharmacy students beginning their professional education revealed a lack of knowledge of proper response to an overdose situation, with 18.56% unfamiliar with the opioid antagonist drug naloxone. Close to 10% (9.58%) of students expressed unwillingness to do anything other than call an ambulance during an overdose event, while 8.98% were either unsure or felt that they would not feel compelled to do something to help. Qualitative coding revealed many barriers to students' becoming capable harm reductionists, including lack of knowledge of substance use, addiction, and harm reduction, in addition to the presence of bias and stigma. Conclusion In order to interrupt the cycle of misinformation and stigma within the larger community and the subgroup of medical providers, gaps in student knowledge must be addressed in meaningful, specific ways over the course of their pharmacy education. Evaluating baseline knowledge and beliefs informs the design of a flexible, action-oriented curriculum to produce well-trained pharmacists ready to engage in finding solutions to the opioid crisis.